2012
DOI: 10.1007/s13201-012-0066-x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of turbidity, COD and BOD from secondarily treated sewage water by electrolytic treatment

Abstract: A preliminary study was conducted for the removal of turbidity (TD), chemical oxygen demand (COD) and biochemical oxygen demand (BOD) from secondarily treated sewage (STS) water through the electrolytic batch mode experiments with DC power supply (12 V) up to 30 min and using a novel concept of electrode combinations of different metals. The different surface areas (40, 80, 120 and 160 cm 2) of the electrodes as a function of cross-sectional area of the reactor and the effect of inter-electrode distances (2.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Escobara et al (2006) have also observed logistical relationship between electrode geometric area (AG) and copper removal efficiency; and accomplished that an increase in copper removal was related to an increase in AG, reaching an optimal value of 35 cm 2 , with an asymptotic value of near 80 %. Chopra and Sharma (2013) observed that with a fourfold increase in the electrode area of Al-Fe i.e. from 40 to 160 cm 2 , the current increased from 0.24 to 0.58 A, which resulted in an increase in the removal percentage of TD, COD and BOD from secondarily treated sewage.…”
Section: Effect Of Electrode Area (Ea)mentioning
confidence: 97%
“…Escobara et al (2006) have also observed logistical relationship between electrode geometric area (AG) and copper removal efficiency; and accomplished that an increase in copper removal was related to an increase in AG, reaching an optimal value of 35 cm 2 , with an asymptotic value of near 80 %. Chopra and Sharma (2013) observed that with a fourfold increase in the electrode area of Al-Fe i.e. from 40 to 160 cm 2 , the current increased from 0.24 to 0.58 A, which resulted in an increase in the removal percentage of TD, COD and BOD from secondarily treated sewage.…”
Section: Effect Of Electrode Area (Ea)mentioning
confidence: 97%
“…Iron more heavy than aluminum induces formation of higher flocks size which offers best solid phase (flocks) to the coagulated pollutants (Bellebia et al, 2012). Iron is a 3d block transition metal that has better complexing properties with inorganic/organic pollutants (Chopra and Sharma, 2013).…”
Section: The Influence Of the Electrode Materials And Combinations On mentioning
confidence: 99%
“…The logistical relationship between electrode geometric area (AG) and Cu removal efficiency and concluded that an increase in Cu removal was related to an increase in AG, reaching an optimal value of 35 cm 2 , with an asymptotic value of near 80 % (Escobara et al, 2006). Chopra and Sharma (2013) observed that with a fourfold increase in the electrode area of Al-Fe from 40 to 160 cm 2 , the CD increased from 0.24 to 0.58 A, which resulted in an increase in the removal percentage of TD, COD and BOD. The maximum removal efficiencies of 81.51 % (TD), 74.36 % (COD) and 70.86 % (BOD) of BTMW were achieved with the use of electrode area of 160 cm 2 and IED of 2.5 cm.…”
Section: Effect Of Electrode Area (Ea)mentioning
confidence: 99%
“…However, sustainable water supply is becoming more challenging by the day due to ever increasing demand of growing population as well as increasing contamination of water resources. At the same time huge quantities of wastewater generated by industries of every hue and kind and also by exponential growth in the number of households are becoming a serious concern for society (Chopra and Sharma, 2013). Sewage treatment consists of an item that deserves ample documentation due to the environmental impact caused by such wastewater if directly discharged into water bodies.…”
Section: Introductionmentioning
confidence: 99%